1996
DOI: 10.1096/fasebj.10.2.8641557
|View full text |Cite
|
Sign up to set email alerts
|

DNA damage and cell cycle checkpoints

Abstract: DNA is prone to numerous forms of damage that can injure cells and impair fitness. Cells have evolved an array of mechanisms to repair these injuries. Proliferating cells are especially vulnerable to DNA damage due to the added demands of cellular growth and division. Cell cycle checkpoints represent integral components of DNA repair that coordinate cooperation between the machinery of the cell cycle and several biochemical pathways that respond to damage and restore DNA structure. By delaying progression thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
140
1

Year Published

1997
1997
2002
2002

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 262 publications
(146 citation statements)
references
References 8 publications
5
140
1
Order By: Relevance
“…HMEC 184 and 184B5 surpassed sham-irradiated levels by 4 h post-irradiation, with 184A1 showing a 70% recovery. Dose-response analyses were conducted at 2 h post-irradiation, a time when inhibition of mitosis is maximal (Kaufmann et al, 1995). A dose of 0.5 Gy yielded an 80 ± 97% decrease in the mitotic fraction in the cell lines examined (data not shown).…”
Section: Mortal and Immortal Hmec Do Not Exhibit A G1 Checkpoint Respmentioning
confidence: 99%
See 1 more Smart Citation
“…HMEC 184 and 184B5 surpassed sham-irradiated levels by 4 h post-irradiation, with 184A1 showing a 70% recovery. Dose-response analyses were conducted at 2 h post-irradiation, a time when inhibition of mitosis is maximal (Kaufmann et al, 1995). A dose of 0.5 Gy yielded an 80 ± 97% decrease in the mitotic fraction in the cell lines examined (data not shown).…”
Section: Mortal and Immortal Hmec Do Not Exhibit A G1 Checkpoint Respmentioning
confidence: 99%
“…Quantitation of G2 delay G2 delay was analysed by quantitating the mitotic fraction as previously described (Kaufmann et al, 1995). Brie¯y, exponentially growing cells were irradiated with 0 ± 2 Gy of ionizing radiation and returned to the incubator.…”
Section: Cell Cycle Analysismentioning
confidence: 99%
“…There is persuasive evidence from the induction of immortality in human ®broblasts that cellular immortality involves the abrogation of both the p53 and RB-1 tumor suppressor gene pathways (Shay et al, 1991;Hara et al, 1991) and decreased regulation of the cell cycle in both G 1 and G 2 (Kaufmann et al, 1995). Although these events are necessary to induce immortality (Wright et al, 1989;Radna et al, 1989) they are still insu cient and a further genetic alteration which activates telomerase (Counter et al, 1992(Counter et al, , 1994) is usually essential.…”
Section: Introductionmentioning
confidence: 99%
“…Human and rodent cells immortalized by a thermolabile T construct cease to proliferate at the nonpermissive temperature, arresting with an increased G2 cell population (Jat and Sharp, 1989; Radna et al, 1989;Mignotte et al, 1990). In addition, recent work by Kaufmann et al (1995) has shown that precrisis human ®broblasts that express T antigen display a reduced mitotic delay following DNA damage. It was unclear, however, whether this e ect was a direct consequence of T antigen expression or was a phenotype acquired during the extended proliferation of genetically unstable T antigen-expressing cell clones.…”
Section: Introductionmentioning
confidence: 99%